Nocturnal panic attacks - Lopes Fabiana L.; Nardi Antonio E.; Nascimento Isabella; Valença Alexandre M.; Zin Walter A (Arquivos de Neuro-Psiquiatria)
The panic-respiration connection has been presented with increasing evidences in the literature. We report three panic disorder patients with nocturnal panic attacks with prominent respiratory symptoms, the overlapping of the symptoms with the sleep apnea syndrome and a change of the diurnal panic attacks, from spontaneous to situational pattern. The implication of these findings and awareness to the distinct core of the nocturnal panic attacks symptoms may help to differentiate them from sleep disorders and the search for specific treatment.